2014
DOI: 10.18517/ijaseit.4.5.423
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Catechin Content in Gambir Powder from Dried Gambir Leaves Quickly using FT NIR PLS Model

Abstract: Conventional production process of gambir often produces gambir with low content of catechin. Engineering of production processes of gambir leaves to produce gambir powder has been developed by previous researchers. The objective of this study was to develop a calibration model to predict the content of catechin in gambir powder from dried gambir leaves quickly using FT-NIR PLS model. Reflectance spectra of gambir powder from dried gambir leaves obtained at a wavelength of 1000 to 2500 nm. Spectra pre-processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…2) by using the sensitivity analysis method in PCA as an input in prior analysis of ANN, it revealed very high value in a correlation of determination (R 2 ≈ 1.00) and very low values in root mean square and misclassification rate (RMSE and MR ≈ 0.00). Nevertheless, the finding of this research is in concordance with the previous study showing the very high value in a correlation of determination (R 2 ≈ 1.00) and very low values in root mean square and misclassification rate (RMSE and MR ≈ 0.00) which indicated that the model is declared the best linear model [29]. Similarly, based on the five hidden node model, it is clear that the SSRSP prediction performance shows an optimum value for the all three indicators.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2) by using the sensitivity analysis method in PCA as an input in prior analysis of ANN, it revealed very high value in a correlation of determination (R 2 ≈ 1.00) and very low values in root mean square and misclassification rate (RMSE and MR ≈ 0.00). Nevertheless, the finding of this research is in concordance with the previous study showing the very high value in a correlation of determination (R 2 ≈ 1.00) and very low values in root mean square and misclassification rate (RMSE and MR ≈ 0.00) which indicated that the model is declared the best linear model [29]. Similarly, based on the five hidden node model, it is clear that the SSRSP prediction performance shows an optimum value for the all three indicators.…”
Section: Resultssupporting
confidence: 92%
“…In this current research, the back propagation neural network (BPNN) model was applied based on the recommendation of previous research [29]. The network architecture of the BPNN consists of three layers namely the input layer, the hidden layer and the output layer [23].…”
Section: Methodsmentioning
confidence: 99%
“…Catechu tannic acid is an anhydrate of catechins [10]. The raw material, the way of processing, and the presence of impurities during the processing determine the amount of tannin content [5], [10]. Tannins are easily bonded with protein and cellulosic fibers because they contain some hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Before main statistical analysis, the total of missing data, data error, and outlier were checked in order to expedite the data analysis [24]. The normality of data distribution, as well as the outliers, were also checked using Kolmogorov-Smirnov and box-plot method [25]. (1) whereas Zij is the jth value of the standardize score of the measured variable i, meanwhile Xij is the observation of jth on the variable i; μ and σ are the mean and the standard deviation of Xij, respectively.…”
Section: Discussionmentioning
confidence: 99%